A novel cost reducing reactive power market structure for modifying mandatory generation regions of producers. (September 2017) - Ahmadimanesh, A.; Kalantar, M.
Abstract: In this paper, a new reactive power market structure is studied and presented. Active power flow by itself causes active and reactive losses. Considering such losses in the reactive power market is the main purpose of this paper. Therefore, this study attempts to improve the reactive power market and create fair competition between producers. To that end, first, a new allocation method for reactive power losses is presented and the contribution of each producer in reactive losses is calculated. In the next step, this share of losses is used to modify the mandatory generation region of units. Then, a new structure is proposed for the reactive power market. This novel structure leads to reduction of system costs in the deregulated power system, which is one of the main policy implications of this paper. Finally, simulations show that the total payment by Independent System Operator will be reduced via application of the proposed methods leading to reduction in system costs. This cost reduction will be significant enough to encourage Independent System Operators to utilize such a structure. In addition, by implementing the new proposed methods, assignment of costs related to reactive power loss will be more justifiable for each generator. Highlights: Proposing a new loss allocation method which is used to declare mandatory generating regions of units. Presenting two new methods for clearing of the reactive power market. Methods rely on eliminating reactive losses of each unit from energy market.